Friction behaviour between a laparoscopic grasper and the large intestine during minimally invasive surgery. Issue 1 (16th November 2021) - Guo, Yan; Cai, Chengmo; Li, Wei
Abstract: Slippage is a common phenomenon between laparoscopic graspers and tissues during minimally invasive surgery, which may lead to inefficient surgical operations, prolonged operation time, and increased patient suffering. The stability factors related to the friction behaviour between laparoscopic graspers and the large intestine, including bio‐surface liquids, pulling angle, and surface profile of graspers, were studied. The friction behaviour at the large intestine–grasper interface was tested using a UMT‐II tribometer under the conditions of clamping force of 1–4 N, sliding displacement of 15 mm, and sliding velocity of 2 mm/s to simulate the grasping and pulling operations of soft tissue. The results showed that the bio‐surface liquid (serum) of the large intestine significantly decreased the friction coefficient, thus reducing the grasping efficiency. A pulling angle of 15° could generate the peak frictional force and enhance the grasping stability. The frictional force increased with the ratio of the profile surface area of the grasper. These results demonstrate that the grasping stability can be improved by changing either the bio‐surface liquid condition or the pulling angle. In addition, a grasper with a larger profile surface area can also prevent slippage due to its significant influence on the pressure distribution and actual contact area for tissue retention.